KETAHANAN EKONOMI MASYARAKAT NELAYAN DI WILAYAH PESISIR SUMATERA BARAT - Novya Zulva Riani; Zul Azhar (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
Groups of fishermen in Padang that fall into the category of lower middle fishermen is a group of owners of fishing vessels with an average income per day is Rp. 579 667, and has a economic resilience of fishermen 225. Groups of fishermen fall into the category of economically active poor fishermen is a group of traditional fishermen with average income per day is Rp. 159 625, and has a economic resilience 102. While a group of fishermen fishing in the category of extremely poor are a group of traditional fishermen who have an average daily income of Rp. 66 221, and has economic resilience 66. So a very vulnerable group can not survive in the condition that caused them not to go to sea is a group of traditional fishermen who are included in the category of economically active poor and extremely poor. Groups of fishermen in Pariaman, which fall into the category of high-income groups (lower middle) is a group of traditional fishermen with average income per day is Rp. 1,128. 298. And fishermen have economic resilience of 304. Groups of fishermen who fall into the category of Economically Active Poor's are a group of traditional fishermen with an average amount of income of Rp. 385 500. and have the economic resilience of fishermen was 286. While the group included fishermen fishing in the extremely poor are a group of fishermen with a large crew average income per day is Rp. 112 032 and has economic resilience 116. So a very vulnerable group can not survive in the condition that caused them not to go to sea is a group of fishermen crew are included in the category of extremely poor. Groups of fishermen in the Pesisir Selatan,  which fall into the category of high-income groups (lower middle) is a group of fishermen crew with average income per day is Rp. 684 600. and have the economic resilience of fishermen 364. Group of fishermen who are included in the category of economically active poor is traditional fishermen with average income per day is Rp. 142.384, and have economic resilience by 111. As for the fishing group strata including low-income category (extremely poor) are a group of fishermen crew with an average income a day is Rp. 56 308 and have the economic resilience of fishermen 69. So a very vulnerable group can not survive in condition that caused them not to go to sea is a group of fishermen crew and fishermen traditionally included in the category of economically active poor and extremely poor.